PEMANFAATAN HARTA BERSAMA DALAM PERKAWINAN PERSPEKTIF KOMPILASI HUKUM ISLAM DAN HUKUM POSITIF - Mustaghfiroh, Siti; Melinda, Nely (Syakhsiyah Jurnal Hukum Keluarga Islam, 2022)
The goal of this research is to figure out the rules of common property use in marriage. Joint property in the juridical concept can be defined as the property of husband and wife obtained during marriage or in other words joint property or commonly called gono gini property is property produced by a couple through cooperation between the throughout the marriage. Husband and wife have the right to use and ownership of the common property. Therefore they both have the same right to use the common property subject to the spouse's approval. This is closely connected to the requirement in “Compilation of Islamic Law Article 92 that a husband or wife may not sell or transfer shared property without the approval of another party”. In the life of society in general, the licensing of the use of common property is still very little realized, especially for common property whose material value does not significantly affect the family economy. The research method used is qualitative, that is, by describing or collecting data sourced from the literature connected to the theory of the provisions of the use of common property in marriage.